PENERAPAN PEMANFAATAN, KUALITAS DAN KEAMANAN SISTEM INFORMASI AKUNTANSI DALAM MENINGKATKAN PENILAIAN KINERJA PERUSAHAAN PT MESHINDO JAYATAMA - Tutik Latifah; Munawaroh (Jurnal Akuntansi dan Bisnis Krisnadwipayana, 2020)
The accounting information system is very important to support the company's success in carrying out its activities. The information which has been available and used by management is very helpful in completing various economic activities, so it is expected to improve the company's performance. It is interesting to further investigate the influence of Accounting Information Systems on Company’s Performance. So the purpose of this research is to find out and analyze the influence of accounting information systems that are focused on the variable Utilization of Accounting Information Systems, Quality of Accounting Information Systems and Accounting Information System Security on company performance with a case study at PT. Meshindo Jayatama. The regression method was used to achieve these objectives. This study used employees with a population of 19 peoples. While the sample taken with a total sampling method was19 peoples. The results of this study indicate that the use of accounting information systems and accounting information system security have a significant effect on company performance. While the quality of accounting information systems does not significantly influence company performance.